Proposta de uma metodologia para a classificação de alternativas de abertura da inovação em pequenas e médias empresas - Peres, Clérito Kaveski (2017)
This study aimed to propose a methodology for the classification of alternatives for opening innovation in Small and Medium Enterprises (SMEs). The structuring of the methodology went through two phases, a first relation to the theoretical basis and a second mathematical basis. On the theoretical basis a bibliographic portfolio was elaborated on the subject that serves as the basis for bibliometric and systematic analyzes. The results of the bibliographic analysis reveal that the literature on topic AI in SMEs, although increasing, is not yet consolidated. Through the systematic analysis of the content of the identified articles 18 alternatives and 29 variables were grouped into 4 criteria related to the process of opening innovation in SMEs. In the mathematical base, second stage, a methodology was structured through the ELECTRE TRI method steps. The methodology has the steps that allow a classification of the alternatives in a structured way, according to the predefined classes. Subsequently, the methodology was implemented, for testing, in 3 companies from different sectors of the economy. The results indicate the different levels of performance in the following criteria: 2.57; 2.37 e; 1.74 for enterprises 1; 2 e; 3, respectively, on a scale of 0 to 4. The result of the classification of alternatives to open innovation in class "A", considered a class more favorable to the company, 50% of the alternatives for the company 1, 28% for the Company 2 and 11% for Company 3. When considering a scenario of improvement, a 10% increase in the weight of the companies' critical criteria was implemented. With this variation 72% of the alternatives for class "A" were adopted for company 1, and 22% for company 3. With this, it can be verified that the increase there is no level of capacity of the companies can lead to an increase Significant reallocated alternatives in upper classes.